Kepatuhan Perawat Dalam Penggunaan Alat Pelindung Diri (APD) dan Perilaku Mencuci Tangan - Ni Luh Suciati; Luh Seri Ani; Dinar Saurmauli Lubis (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2023)
Background: Cases of COVID-19 patients are increasing every day. The psychological impact felt by nurses was anxiety, fear, depression and a high risk of contracting COVID-19. Recommendations for preventing the risk of transmission are the use of PPE and hand washing behavior. Although PPE as a means of preventing the virus transmission, there are still nurses who do not comply with using it. Purpose: The purpose of the study was to determine the adherence of nurses in using PPE and hand washing behavior. Methods: This study is an analytic cross-sectional study, with a sample of 100 people in the isolation ward of Karangasem General Hospital. Data were analyzed by chi square test by lookcing at value, odds ratio (OR) and adjusted odds ratio (AOR). Results: 55% nurses use PPE in the obedient category, 52% nurses' hand washing behavior in the obedient category. Conclusions: Most are compliant in using PPE and washing hands.